2010
DOI: 10.1002/anie.200904858
|View full text |Cite
|
Sign up to set email alerts
|

Single Molecules as Optical Nanoprobes for Soft and Complex Matter

Abstract: The optical signals of single molecules provide information about structure and dynamics of their nanoscale environment, free from space and time averaging. These new data are particularly useful whenever complex structures or dynamics are present, as in polymers or in porous oxides, but also in many other classes of materials, where heterogeneity is less obvious. We review the main uses of single molecules in studies of condensed matter at nanometer scales, especially in the fields of soft matter and material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 153 publications
(147 reference statements)
0
35
0
Order By: Relevance
“…The method is based on optical detection and analysis of fluorescence from spatially isolated immobilized molecules in extremely diluted samples. Examples of applications of single-molecule spectroscopy in the study of physical and chemical properties and processes in soft matter and polymers can be found in recent reviews [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The method is based on optical detection and analysis of fluorescence from spatially isolated immobilized molecules in extremely diluted samples. Examples of applications of single-molecule spectroscopy in the study of physical and chemical properties and processes in soft matter and polymers can be found in recent reviews [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from biological applications, single-molecule spectroscopy has provided exceptional insights into the properties of soft and complex materials, and holds great promise for further development in this fi eld. For recent reviews, see Refs [3][4][5][6][7][8]. Th ere will, no doubt, be further qualitative progress related to recently developed super-resolution microscopic techniques [9][10], which overcome the diff raction limit in optical imaging and bring the resolution closer to the molecular scale.…”
mentioning
confidence: 99%
“…Knowledge of the physical properties of a single chain helps us to understand the properties of polymer nanostructures and leads to an advanced understanding of the macroscopic (bulk) state of the polymers. Th is review will focus on single polymer chains and will not deal with single small molecules as probes of polymer dynamics, which although an important area of research, has been well covered [6,7]. Th e review is further confi ned to the use of far-fi eld fl uorescence microscopy, excluding non-optical scanning probe methods as well as near-fi eld optical microscopy, and to spectroscopic studies performed at room temperature.…”
mentioning
confidence: 99%
“…However, IET processes are usually very complex due to high dependence on its local environments. Single-molecule spectroscopy has led to many surprises and has now become a standard technique to study complex structures (Kulzer et al, 2010) (Yang et al, 2003). Single-molecule studies of photosensitized electron transfers on dye containing nanoparticles also showed fluorescence fluctuations and blinking, and the fluctuation dynamics were found to be inhomogeneous from molecule to molecule and from time to time (Funatsu et al, 1995).…”
Section: Manipulation Of Interfacial Electron Transfer Dynamicsmentioning
confidence: 99%